Challenges in installing interlocking brick system for residential building in Perak State / Awal Hasrizwan Awaluddin and Mariaty Mohd Bahari - Awaluddin, Awal Hasrizwan; Mohd Bahari, Mariaty (2019)
This paper intends to discuss the methods of construction for the interlocking bricks system in Perak. This study also discussing the challenges and barriers in installing interlocking brick system in residential development. Qualitative methods are applied by recording structured interviews for construction of interlocking brick system and the benefits of owning this construction method system house in Perak area.